2019
DOI: 10.3390/electronics8040451
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Channel Optoelectronic Measurement System for Soil Nutrients Analysis

Abstract: To solve the problems that occur when farmers overuse chemical fertilizers, it is necessary to develop rapid and efficient portable measurement systems for the detection and quantification of nitrogen (N), phosphorus (P), and potassium (K) in soil. Challenges arise from the use of currently available portable instruments which only have a few channels, namely measurement and the reference channels. We report on a home-built, multichannel, optoelectronic measurement system with automatically switching light sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Other related applications that can involve biometrics have been presented in [9][10][11][12][13]. The authors propose interesting detection and recognition approaches with applications in the domain of watermarking [9], health [10][11][12], and nutrients analysis [13]. We found that the ideas of the proposed contributions for data processing, feature extraction, learning, and embedded systems, seem interesting to be considered in the field of biometrics.…”
Section: In This Special Issuementioning
confidence: 97%
See 1 more Smart Citation
“…Other related applications that can involve biometrics have been presented in [9][10][11][12][13]. The authors propose interesting detection and recognition approaches with applications in the domain of watermarking [9], health [10][11][12], and nutrients analysis [13]. We found that the ideas of the proposed contributions for data processing, feature extraction, learning, and embedded systems, seem interesting to be considered in the field of biometrics.…”
Section: In This Special Issuementioning
confidence: 97%
“…Other related applications that can involve biometrics have been presented in [9][10][11][12][13]. The authors propose interesting detection and recognition approaches with applications in the domain of watermarking [9], health [10][11][12], and nutrients analysis [13].…”
Section: In This Special Issuementioning
confidence: 99%
“…(continued from previous page) measurements. 10 Based on the Beer-Lambert law, relatively high correlation peaks were obtained between the absorption at the emission wavelength and their respective nutrient concentration in the soil sample. Similarly, Shibusawa employed a multi-sensor system to measure moisture content, soil organic matter, nitrate nitrogen, pH, and electrical conductivity for a field depth of 15-40cm.…”
Section: Venkadesh Et Almentioning
confidence: 99%
“…Therefore, it is important to normalize the measurement of -N in soil ( Cho et al, 2018 ; Richa et al, 2021 ). Considering the concentrations of -N in soil is readily influenced by environmental factors and changes rapidly, it is necessary to perform in situ measurement to evaluate the non-point source pollution ( Wang et al, 2015 ; Ma et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%